Fetoplacental Discrepancy with Normal Karyotype in Amniotic Fluid and Two Different Cell Lines in Placenta - Veronica Ortega; Christina Mendiola; Eric Williamson; Kenneth Higby; Gopalrao V. N. Velagaleti (Case Reports in Genetics)
We present a case of fetoplacental discrepancy in a second-trimester fetus with normal karyotype in amniotic fluid and two different Robertsonian translocations in placenta. A 41-year-old woman of Middle-Eastern origin, gravida 2, para 1, underwent amniocentesis at 16-week gestation because of advanced maternal age. Amniotic fluid karyotype showed a normal 46,XX karyotype with a homozygous inv(9). Parental chromosome analysis showed both parents to be carriers of inv(9) and the parents are not consanguineous. Fetal ultrasound was normal. The mother presented to the clinic 4 weeks later with intrauterine fetal demise. Chromosome analysis from the placenta showed two different cell lines: a balanced (15;21) Roberstonian translocation in 11 cells and an unbalanced (21;21) Robertsonian translocation in 9 cells. The karyotype was interpreted as mos 45,XX,inv(9)(p11q13)x2,der(15;21)(q10;q10)[11]/46,XX,inv(9)(p11q13)x2,+21,der(21;21)(q10;q10). Mother was a carrier for the Cystic Fibrosis (delta F508), Factor V Leiden mutations, HbD-Los Angeles and HbQ-India variants. She also had a sibling with term stillbirth. Her husband’s history was unremarkable. Our case appears to be another example of confined placental mosaicism (CPM) with normal fetal karyotype. However, we could not confirm the possibility that CPM contributed to the IUFD in our case given the complex medical history of the mother.